2013
DOI: 10.1038/srep02080
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Visible Light-Induced O2 Generation by Self-Assembled Nanohybrids of Inorganic Nanosheets and Polyoxometalate Nanoclusters

Abstract: Unusually high photocatalytic activity of visible light-induced O2 generation can be achieved by electrostatically-derived self-assembly between exfoliated Zn-Cr-LDH 2D nanosheets and POM 0D nanoclusters (W7O246− and V10O286−) acting as an electron acceptor. This self-assembly can provide a high flexibility in the control of the chemical composition and pore structure of the resulting LDH-based nanohybrids. The hybridization with POM nanoclusters remarkably enhances the photocatalytic activity of the pristine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(33 citation statements)
references
References 40 publications
1
32
0
Order By: Relevance
“…1a). The powder XRD patterns of materials are shown in A c c e p t e d M a n u s c r i p t 8 definite loading amount of CdS for such a pillared structure suggests that the nanohybrid's composition is dependant on the surface charge ratio of the guest CdS nanoparticle to the host LDHs nanosheet, as previously reported [21]. As displayed in Fig.…”
Section: Structural Analysessupporting
confidence: 77%
See 1 more Smart Citation
“…1a). The powder XRD patterns of materials are shown in A c c e p t e d M a n u s c r i p t 8 definite loading amount of CdS for such a pillared structure suggests that the nanohybrid's composition is dependant on the surface charge ratio of the guest CdS nanoparticle to the host LDHs nanosheet, as previously reported [21]. As displayed in Fig.…”
Section: Structural Analysessupporting
confidence: 77%
“…A c c e p t e d M a n u s c r i p t 4 well-developed nanohybrids assembled by the exfoliated titanate nanosheets and oxide nanoparticles [10][11][12][13]20], the reports on the materials fabricated by the exfoliated LDH nanosheets and sulfide nanoparticles are very rare [14,21]. In this work, a new CdS-pillared CoAl-LDH nanohybrid was prepared by simply mixing the positively charged 2D nanosheets of CoAl-LDH and the negatively charged CdS nanosol suspensions.…”
Section: Page 4 Of 20mentioning
confidence: 99%
“…2A). The isotherms and hysteresis behaviors of CZCs can be assigned as BDDT-type IV and IUPAC-H2 type hysteresis loop [34,35], which is characteristic of mesoporous materials having a high energy of adsorption and the presence of well-ordered pores with narrow and wide sections and interconnecting channels [25,35]. Compared with CZCs, ZnCr-LDH shows a steep adsorption branch at high p$p 0 À1 region and a sloping desorption branch, which corresponds to type H3 by IUPAC classification [34].…”
Section: Structural Analysesmentioning
confidence: 99%
“…Garcia et al firstly reported the high photocatalytic activity of ZnCr-LDH for O 2 generation [22]. Subsequently, it was found that NiTi-LDH [23], ZnCr-LDH/graphene [24], ZnCr-LDH/ layered titanate [2], ZnCr-LDH/polyoxometates [25], and NiTi-LDH/graphene composites [26] have efficient photocatalysis for O 2 evolution. However, there are only a few reports about photocatalytic water splitting into H 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation